Radiation-induced effects in silicon - Gaidar, G.P.; Pinkovska, M.B.; Starchyk, M.I. (Вопросы атомной науки и техники, 2019)
Results of complex studies of the structural properties of silicon irradiated with light ions of megaelectronvolt energies by fluences greater than 10¹⁶ cm⁻² are presented. It was found that during irradiation under conditions of large energy release in thin layer of crystal, the favorable conditions can be created for the controlled introduction of structural defects and the appearance of the effects of ordering and long-range. The possibility of layer-by-layer modification of the properties of silicon at depths up to 780 μm under irradiation with ions was established that can be used to provide the actual needs of micro- and nanoelectronics.